The Influence of Self-Concept with Emotional Abuse on Early Dating Adults - Haekalrini Saputri, Agita; Rahmat Hidayat, Dede (Rifa'Institute, 2023)
Introduction: in dating relationships, many people experience conflicts due to differences of opinion. In order to maintain relationships, women sometimes experience or commit emotional violence while dating, both consciously and unconsciously. Meanwhile, men can also be emotionally harassed while dating women. Objective: the purpose of this study was to confirm the influence of self-concept with emotional abuse on early adults who were dating or had been in a relationship. Method: this research was conducted with a quantitative approach. The data collection method in this study used two instruments used in this study, namely the Self concept scale and the Emotional abuse scale which was disseminated using google forms. The data analysis technique used is simple linear regression with non-parametric analysis. Results and Discussion: this study there was a negative influence between self-concept and emotional violence in early adults dating in Bekasi, the R square2 value was 0.123 (p = 0.01) and there was an influence value of 12.3% indicating that the two variables had a negative influence and had opposite directions. Conclusion: These results indicate that the higher a person's self-concept, the lower the level of emotional abuse experienced